Effect of Shaking Speed and Type of Closure on Shake Flask Cultures - McDaniel, L. E. (1969)
Growth of microorganisms and biosynthesis of microbial products in shake flasks may be limited by operating conditions which provide inadequate supplies of oxygen. Methods are described for meeting the oxygen requirements of test organisms by using standard baffled flasks with pad-type closures and shaking at relatively high speeds. Growth of Escherichia coli B in a rich medium and production of candidin by Streptomyces viridoflavus were the test systems used. Flasks shaken at 230 to 385 rev/min gave sulfite oxidation rates of 1 to 8 mmoles of oxygen per liter per min over a useful working volume range (40 to 150 ml in 300-ml flasks). These rates are as high as those obtained in agitated fermentors under usual operating conditions.